Filsafat Komunikasi - Rapi Lamnur Siregar; Indira Fatra Deni P; Hasnun Jauhari Ritonga (Lembaga Pengembangan Kinerja Dosen, 2024)
This research explores the theoretical and philosophical underpinnings of the communication process, with a particular focus on the ethical implications and strengths in contemporary communication practice. In the context of the evolution of philosophical thought, this study combines various classical and modern communication theories. Through a qualitative approach, this study collected data from various literature studies such as books, communication journals and discourse analysis from key texts. The findings suggest that communication is not only a means of delivering messages but also as a mechanism of identity and power formation. In addition, the study revealed that communication ethics, especially in digital media, require special attention to address the challenges of honesty, transparency, and privacy. The study contributes to a deeper understanding of how philosophical principles can be applied to improve communication practices in the digital age. Thus, this study emphasizes the importance of philosophical reflection in the face of the complexity of modern communication and its impact on society